Enhanced phycocyanin production of Arthrospira maxima by addition of mineral elements and polypeptides using response surface methodology - Yao, Ting; Huang, Jianke; Su, Bocheng; Wei, Liang; Zhang, Ai-Hua; Zhang, Dao-Feng; Zhou, Yongsheng; Ma, Guangyuan (Frontiers in Marine Science, 2022)
Introduction As a pigment protein, phycocyanin has been widely used in the fields of food, nutraceutical and biotechnology due to its excellent biological activities of antioxidant. So far, Arthrospira has been generally considered as a great species for phycocyanin production. Methods In this study, independent and interactive effect of three factors, NaCl, Bainengsi (BS) and Bainengtai (BT) on microalgae growth and phycocyanin production were explored by response surface methodology (RSM). Using Box-Behnken design (BBD) method, the well-fitting quadratic models were established based on experimental results. Results Moreover, the maximum phycocyanin concentration reached 704.66 mg L-1 at the optimal condition (185 mM NaCl, 200 mg L-1 BS, and 20 mg L-1 BT), while the maximum phycocyanin content of 19.03% was obtained at another optimal condition (136 mM NaCl, 200 mg L-1 BS, and 50 mg L-1 BT). Compared to control, the concentration and content of phycocyanin were increased by 22.98% and 16.73%, respectively. Discussion Overall, this study demonstrated that addition of exogenous substances (BS, BT) into culture medium optimized by RSM was an effective approach to increase phycocyanin production, which paved a potential way to realizing high efficient production of algal biomass and bioactive substances.